Study of the Arrhythmogenic Profile in Dogs with Acute and Chronic Monocytic Ehrlichiosis - Latini, Carolina Dragone [UNESP]; Alfonso, Angélica [UNESP]; Filippi, Maurício Gianfrancesco [UNESP]; Lima, Mayra de Castro Ferreira [UNESP]; Paes, Antônio Carlos [UNESP]; Corrêa, Jaqueline Valença [UNESP]; Santos, Beatriz Almeida [UNESP]; Tsunemi, Miriam Harumi [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (MDPI, 2025)
Canine monocytic ehrlichiosis (CME) is a globally prevalent disease transmitted by the tick Rhipicephalus sanguineus and caused by the Gram-negative bacterium Ehrlichia spp. Following an incubation period, the infection is categorized based on the progression of the disease into acute, subclinical, and chronic stages. Besides hematological alterations, the cardiovascular system is significantly impacted by the hemodynamic effects of the disease, as persistent anemia can lead to myocardial hypoxia and the activation of inflammatory processes, potentially causing myocarditis. It is known that in dogs infected with Ehrlichia canis, there is a higher occurrence of arrhythmias and a predominance of sympathetic activity. This study assessed arrhythmogenic parameters, including P wave dispersion (Pd), QT dispersion (QTd), and QT instability, along with heart rate variability (HRV) analysis from 24 h Holter monitoring in naturally infected dogs during the acute phase (n = 10) and chronic phase (n = 10) compared to a control group (n = 10). The Pd and QTd values were higher in the infect group, confirming the arrhythmogenic character. Instability parameters (TI, LTI, and STI) were higher in sick animals, but no worsening was observed in the chronic phase. All HRV metrics in the time domain were higher in the control group, indicating a balanced sympathovagal activity throughout the day in healthy dogs. Additionally, parameters linked to parasympathetic activity (rMSSD and pNN50) were reduced in the sick groups, confirming the dominance of sympathetic activity. These findings indicate a decrease in HRV in sick individuals and reinforce this useful marker for assessing the influence of the autonomic nervous system on the cardiovascular system. In conclusion, CME exhibits arrhythmogenic activity characterized by the deterioration of predictive parameters for ventricular arrhythmias and increased activity of the sympathetic autonomic nervous system in the heart. This is likely secondary to myocarditis, myocardial hypoxia, and structural damage to cardiomyocytes.
Keywords: arrhythmias; arrhythmogenesis; canine hemoparasitosis; electrocardiogram; Holter